Letter from Charles Lever to A. W. Thayer with invitation to dinner, dated Monday, May 4 [1868?] - Lever, Charles, 1806-1872:::::::::::::::; Thayer, Alexander Wheelock, 1817-1897 (recipient)::::::::::::::: (2023)
Autograph letter signed from Charles Lever to A. W. Thayer with invitation to a family dinner, with Capt. Thony as another guest, dated Monday, May 4 [1868?], with hand-addressed envelope.